Clinical Presentation of Acute Appendicitis in Patients With Agenesis of the Vermiform Appendix - Alexander A. Andreev; Alexander A. Glukhov; Alexander V. Gorlunov; Anastasia Yu. Laptiyova; Anton P. Ostroushko (Инновационная медицина Кубани, 2025)
This article analyzes 10 cases of agenesis of the vermiform appendix with clinical presentation of acute appendicitis. Given that this pathology occurs in 1 of 100000 surgical interventions for acute appendicitis according to the literature, it can be assumed that this number of observations was based on the analysis of the results of 1 million interventions.The article reports clinical (including intraoperative), laboratory, and imaging findings and gives recommendations for detection of agenesis of the vermiform appendix and treatment of abdominal pain syndrome.